Problems with defining cannabis dependence. Issue 1 (January 2020) - Hamilton, Ian; Tracy, Derek
Abstract : Purpose of review: Cannabis enjoys a unique social status, widely perceived as a relatively harmless drug, with several benefits reported by the people who use it. Several jurisdictions have opened up access to cannabis to their populations for medicinal and/or recreational reasons. Given this changing regulatory environment, this article is intended to prompt debate about what is known about cannabis dependence and what has still to be revealed. Recent findings: Evidence suggests that 1 in 10 cannabis users are at risk of developing dependence. However, investigation of the way risk is estimated and the diagnosis of cannabis use disorder is constructed highlight some methodological problems, which call into question the incidence and prevalence of this diagnosis. Summary: There is scope to improve the way cannabis dependence is defined and counted in at-risk populations. Improving our understanding of this risk could lead to identifying who might be at risk of developing dependence prior to exposure to the drug.